AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING COMPREHENSION AT THE EIGHT GRADE OF SMP NEGERI 3 DUHIADAA - Kisno, Neng Putri (Journal of Education and Teaching Learning, 2024)
This research aimed to identify difficulties and determine the factors that cause problems for class VIIIa students in reading comprehension at SMP Negeri 3 Duhiadaa. This research was mixed methods, namely qualitative and quantitative methods, data collection methods were tests and interviews, and data analysis methods were data reduction and data display. The research results showed four difficulties faced by class VIIIa students in finding the main idea there were 21.34% of students experienced difficulty understanding, with a score of 38. Then, 33.14% of students experienced difficulty understanding vocabulary, scoring 59. Then, 22.47% of students needed help making conclusions with several errors 40. Furthermore, 23.03% of students needed help finding detailed information with several mistakes 41. Factors causing students' difficulties in reading comprehension were difficulties understanding long sentences in texts, instructions from inadequate teachers, challenges in understanding vocabulary, home environment, and school environment.